Psychosomatic aspects of obesity as a risk factor of metabolic syndrome - A. G. Babin; E. A. Chechetkina; I. E. Koltunov (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the role of obesity (O), as a psychopathological disorder, in metabolic syndrome (MS) development; to assess the effectiveness of psychotherapeutist’s participation in MS prevention and treatment. Material and methods. The presence and stage of O was assessed by body mass index (BMI). The study included 3 groups: Group I – patients with bulimia nervosa and O (n=64), including individuals with cardiovascular disease, CVD (n=12); Group II – patients with CVD, but without O or psychopathology (n=28); Group III – patients with CVD and with or without O, MS, and diabetes mellitus, DM (n=78). Group III was divided into 4 subgroups by symptom severity. In Groups I and II, psychological profile was assessed by clinical interview and MMPI test; in Group III, all MS components were measured, including lipid and glucose metabolism parameters. Results. In Groups I and II, CVD patients, regardless of concomitant O, had similar MMPI profiles, with maximal scores for scale 1 (hypochondria), which was different from the profile of bulimic patients in Group I. In Group II, in contrast to Group I and CVD subgroup, a tendency towards weight reduction in more advanced age was observed. The same tendency was also observed in 3 subgroups of Group III, being the strongest in the subgroup with the most severe symptoms (MS and DM). In all 4 subgroups of Group III O as a specific MS component, preceding the other MS symptoms, but independent from them in the case of developed MS. Conclusion. The only effective method for MS prevention is psychotherapeutic diagnostics and treatment of O at the stage preceding the development of metabolic disturbances. In the treatment of MS patients, the role of psychotherapeutist is complementary, being aimed at weight reduction by treating eating disorders.